Antenatal umbilical coiling index in gestational diabetes mellitus and non-gestational diabetes pregnancy - Laily Najafi; Mohammad E. Khamseh; Maryam Kashanian; Ladan Younesi; Azadeh Abedini; Ameneh Ebrahim Valojerdi; Zahra Amoei; Elmira Nouri Khashe Heiran; Abbas Ali Keshtkar; Mojtaba Malek (Elsevier, 2018)
Objective: Umbilical cord abnormalities increase fetal morbidity and mortality. This study was designed to compare antenatal umbilical coiling index (aUCI) in gestational diabetes mellitus (GDM) and non-gestational diabetes mellitus (non-GDM) pregnancy, considering uncertainties about the best time to perform antenatal ultrasonography scan. Materials and Methods: In this prospective study, 246 parturients were included, 123 with GDM and 123 with non-GDM pregnancy. Gestational diabetes was confirmed at 24-28 weeks of gestation (WG) using one-step strategy. An anatomical ultrasound survey of placenta and umbilical cord was performed at 18-23 as well as 37-41 weeks of gestational age. Results: At 18-23 WG, the frequency distribution (10th, 90th percentiles, mean ± SD) of the aUCI in the GDM and non-GDM groups were (0.13,0.66,0.32 ± 0.19) and (0.18,0.74, 0.4 ± 0.31) respectively. These values were (0.12,0.4, 0.25 ± 0.11) in the GDM group at 37-41 WG and (0.17,0.43, 0.29 ± 0.11) in the non-GDM group. A significant relationship was detected between UCI value and GDM/non-GDM groups at both antenatal evaluations (18-23 WG; P = 0.002, 37-41WG; P < 0.001). A significant association at 18-23 WG was found between GDM/non-GDM groups and aUCI categorization (hypocoiling <10th, normocoiling 10th-90th and hypercoiling >90th) (P = 0.001). However, hypocoiling were significantly more frequent in GDM than non-GDM in both antenatal evaluations (P < 0.001, P = 0.006). Conclusion: Antenatal UCI in pregnancy complicated by GDM were lower in comparison with non-GDM pregnancy. The most abnormal pattern of coiling in gestational diabetes was hypocoiling in both trimesters. In addition, 18-23 WG is the best time to perform ultrasound scan to detect aUCI and umbilical cord pattern. Keywords: Antenatal, Gestational diabetes mellitus, 75-g oral glucose tolerance test, Ultrasonography, Umbilical coiling index